2015
DOI: 10.12740/app/58746
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity, femininity, self-appeal, strategies of self-presentation and styles of interpersonal functioning in transsexual women

Abstract: SummaryAim. The aim of this study was to explore potential differences in gender identity and interpersonal functioning styles between transsexual and non-transsexual women. Method. The following tests were used: Bem Sex Role Inventory (Polish version), Self-Appeal Scale, Interpersonal Styles Scale, and the Strategies of Self-Presentation Questionnaire. The study group consisted of 32 adult transwomen, mean age 35.09 years. The control group consisted of 32 adult cissexual women (mean age 31.69 years) selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Males and females show themselves differently (Bowman & Compton, 2014;Felmlee, Sweet, & Sinclair, 2012). Moreover, trans and lesbians perform their identities and sexual orientations in a manner that enhances their being (Mandal & Hillman, 2013;Mandal & Jakubowski, 2015;Rosario, Schrimshaw, & Hunter, 2008;Tortajada, Arauna, & Martinez, 2013). No definitive study has found the gender demarcation stable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Males and females show themselves differently (Bowman & Compton, 2014;Felmlee, Sweet, & Sinclair, 2012). Moreover, trans and lesbians perform their identities and sexual orientations in a manner that enhances their being (Mandal & Hillman, 2013;Mandal & Jakubowski, 2015;Rosario, Schrimshaw, & Hunter, 2008;Tortajada, Arauna, & Martinez, 2013). No definitive study has found the gender demarcation stable.…”
Section: Literature Reviewmentioning
confidence: 99%